Non-fragile event-triggered control of positive switched systems. (14th September 2021) - Wu, Yanqi; Zhang, Junfeng
This paper presents a non-fragile event-triggered control approach to positive switched systems without/with input saturation. First, a 1-norm based on event-triggered mechanism is established for positive switched systems. By using the matrix decomposition technique, a non-fragile controller based on event triggered mechanism is designed for positive switched systems without saturation. Then, the presented non-fragile event-triggered control design approach is developed to positive switched systems with saturation. The saturation term is transformed into interval form and a controller is designed by means of the linear programming. The positivity and stability of the closed-loop systems are guaranteed under the designed controllers. Finally, a numerical example is given to illustrate the effectiveness of the design.